Existence and uniqueness of solution of free boundary problem with partially degenerate diffusion. (August 2020) - Liu, Siyu; Wang, Mingxin
Abstract: In this paper, we mainly introduce a general method to study the existence and uniqueness of solution of free boundary problems with partially degenerate diffusion.